Sounds of a Community: Cultural Identity and Interactive Art. - Gluck, Robert J. (Leonardo Music Journal, 2005)
Sounds of a Community (2001–2003), a sound installation, is a series of sculptures modeled upon traditional Jewish ritual objects. The sculptures also serve as musical instruments. The installation is designed to offer an engaging musical experience but also a means by which people can explore complex issues relating to religious and cultural identity. Basic issues involved in the design, construction and programming of this work are presented, along with an exploration of how this work seeks to engage visitors in questions about their relationship to religious settings that involve the place of an individual within a group.